2019
DOI: 10.1016/j.respol.2018.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Greater adaptivity or greater control? Adaptation of IOR portfolios in response to technological change

Abstract: This paper addresses the question of how firms accomplish the strategic task of adapting their entire set of IORs (interorganizational relationships) to changing environmental conditions. To study this, we move beyond the focus on collaboration with individual partners (the dyadic perspective) that has been the dominant emphasis in the literature until now. Instead, we view the firms' portfolios through the lens of the different modes of IOR engaged in (licensing agreements, non-equity alliances, venture capit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 115 publications
(203 reference statements)
1
20
0
Order By: Relevance
“…Recent exceptions have taken this perspective, indicating scholars' evolving interest in the organizational context. Investigating how firms adapt their interorganizational relationships to changing environmental conditions, de Leeuw et al (2019) found that firms adjust their portfolio diversity. Koryak et al (2018) and Revilla and Rodríguez-Prado (2018) studied the tensions arising from exploration and exploitation and demonstrated firms' ambidextrous solutions to address these tensions (see also Crescenzi and Gagliardi, 2018).…”
Section: Interorganizational Policy Studies On How Firms Organize Expmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent exceptions have taken this perspective, indicating scholars' evolving interest in the organizational context. Investigating how firms adapt their interorganizational relationships to changing environmental conditions, de Leeuw et al (2019) found that firms adjust their portfolio diversity. Koryak et al (2018) and Revilla and Rodríguez-Prado (2018) studied the tensions arising from exploration and exploitation and demonstrated firms' ambidextrous solutions to address these tensions (see also Crescenzi and Gagliardi, 2018).…”
Section: Interorganizational Policy Studies On How Firms Organize Expmentioning
confidence: 99%
“…Finally, future research should explore how firms' interorganizational relationships affect their design of internal organizational structures for exploration. Recent research has explored how firms adapt their portfolios of interorganizational relationships to changing environmental conditions (de Leeuw et al, 2019). Future research should investigate how firms' interorganizational relationships influence their internal organizational designs, a direction that could add depth to our model.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Another stream of studies has focussed on investigating the portfolio of enterprises (de Leeuw et al , 2019; Ferrand et al , 2009). Such research has found that pharmaceutical firms tend to widen their portfolio of inter-organisational relationships under uncertain external technological environments (de Leeuw et al , 2019).…”
Section: Thematic Focimentioning
confidence: 99%
“…Further, given the dynamic landscape and ever-mutating business needs, scholars have increasingly focussed on understanding how businesses work with one another, especially over the past two decades. Within this body of literature, B2B relationships in industries such as health care have received notable attention (de Leeuw et al , 2019; Roijakkers et al , 2005). Interestingly, the majority of the existing studies on B2B relationships in health care have examined the R&D alliances of pharmaceuticals firms (Diestre and Rajagopalan, 2012; Djurian et al , 2020; Zeng et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Since practitioners' focus on network/ecosystem management occurred after scholars had moved along their theory diffusion cycle, scholars have decreasing needs to collaborate with organizations now grappling with managing their own network. Consistent with the theory diffusion cycle, most recent academic work on networks has become dependent on large datasets, which makes it harder for practitioners to interest scholars in collaboration, especially since academics and journals are oriented toward quantitative studies (Alvesson & Sandberg, 2013;de Leeuw et al, 2019;Glynn & Raffaelli, 2010). On the other hand, scholars are beginning to translate their findings for practitioners, who still are in the exploratory phase of their diffusion cycle and, hence prone to look outside their industry for ideas (Chandler & Hwang, 2015;Greve, 2005).…”
Section: Research-before-practice Diffusionmentioning
confidence: 99%